No Hiking Beyond this Point! Hiking Risk Prevention Recommendations in Peer-Reviewed Literature. (December 2017) - Kortenkamp, Katherine V.; Moore, Colleen F.; Sheridan, Daniel P.; Ahrens, Emily S.
Abstract: Outdoor recreation in wild areas has many benefits, but also poses risks. We conducted a systematic review of the prevention recommendations in peer-reviewed articles about hiking incidents (injury, illness, or need for rescue) published between 1970 and 2015. Searches in PubMed, Web of Science, and Engineering Village yielded 91 articles after screening for relevance. A total of 559 prevention recommendations were extracted from articles. The foci of the recommendations were categorized using a systems-oriented approach to accident prevention, an adapted Haddon matrix. Five non-mutually exclusive categories were used: hiker, groups and relationships, agent inducing the incident, institutions and sociocultural practices, and equipment. We also coded prevention recommendations that pertained to education within each of the five categories. Sixty percent of the prevention recommendations focused on changing the hiker's decisions and behaviors, and 39% referred to institutions and sociocultural practices. Few addressed the social influences of groups and relationships (8%), equipment (16%), or the agent of harm (16%). Education was the focus of 27% of the recommendations. We conclude that effective prevention needs to include multiple aspects of outdoor recreation systems and their interactions with the hiker's behavior and characteristics. Management implications: This systematic review introduces outdoor recreation managers to the systems-oriented Haddon matrix framework for accident prevention in outdoor recreation. By using this framework, this paper: 1. Views accidents as resulting from interactions of individuals with both social and physical environments. 2. Highlights areas for prevention that tend to be missing from published safety recommendations (groups, agent of harm, and equipment). 3. Gives examples of how managers can look at outdoor risk prevention from a broader perspective in order to find innovative solutions to common accidents and rule violations.